Colchicine in Patients With Coronary Artery Disease: A Systematic Review and Meta‐Analysis of Randomized Trials - Kofler, Thomas; Kurmann, Reto; Lehnick, Dirk; Cioffi, Giacomo Maria; Chandran, Sujay; Attinger‐Toller, Adrian; Toggweiler, Stefan; Kobza, Richard; Moccetti, Federico; Cuculi, Florim; Jolly, Sanjit S.; Bossard, Matthias (Journal of the American Heart Association, 2021)
Background Inflammation plays a pivotal role in coronary artery disease (CAD). The anti-inflammatory drug colchicine seems to reduce ischemic events in patients with CAD. So far there is equipoise about its safety and impact on mortality. Methods and Results To evaluate the utility of colchicine in patients with acute and chronic CAD, we performed a systematic review and meta-analysis. MEDLINE, EMBASE, Cochrane CENTRAL and conference abstracts were searched from January 1975 to October 2020. Randomized trials assessing colchicine compared with placebo/standard therapy in patients with CAD were included. Data were combined using random-effects models. The reliability of the available data was tested using trial sequential analyses . Of 3108 citations, 13 randomized trials (n=13 125) were included. Colchicine versus placebo/standard therapy in patients with CAD reduced risk of myocardial infarction (odds ratio [OR] 0.64; 95% CI, 0.46-0.90; P=0.01; I2 41%) and stroke/transient ischemic attack (OR 0.50; 95% CI, 0.31-0.81; P=0.005; I2 0%). But treatment with colchicine compared with placebo/standard therapy had no influence on all-cause and cardiovascular mortality (OR 0.96; 95% CI, 0.65-1.41; P=0.83; I2 24%; and OR 0.82; 95% CI, 0.55-1.22; P=0.45; I2 0%, respectively). Colchicine increased the risk for gastrointestinal side effects (P<0.001). According to trial sequential analyses, there is only sufficient evidence for a myocardial infarction risk reduction with colchicine. Conclusions Among patients with CAD, colchicine reduces the risk of myocardial infarction and stroke, but has a higher rate of gastrointestinal upset with no influence on all-cause mortality.Background Inflammation plays a pivotal role in coronary artery disease (CAD). The anti-inflammatory drug colchicine seems to reduce ischemic events in patients with CAD. So far there is equipoise about its safety and impact on mortality. Methods and Results To evaluate the utility of colchicine in patients with acute and chronic CAD, we performed a systematic review and meta-analysis. MEDLINE, EMBASE, Cochrane CENTRAL and conference abstracts were searched from January 1975 to October 2020. Randomized trials assessing colchicine compared with placebo/standard therapy in patients with CAD were included. Data were combined using random-effects models. The reliability of the available data was tested using trial sequential analyses . Of 3108 citations, 13 randomized trials (n=13 125) were included. Colchicine versus placebo/standard therapy in patients with CAD reduced risk of myocardial infarction (odds ratio [OR] 0.64; 95% CI, 0.46-0.90; P=0.01; I2 41%) and stroke/transient ischemic attack (OR 0.50; 95% CI, 0.31-0.81; P=0.005; I2 0%). But treatment with colchicine compared with placebo/standard therapy had no influence on all-cause and cardiovascular mortality (OR 0.96; 95% CI, 0.65-1.41; P=0.83; I2 24%; and OR 0.82; 95% CI, 0.55-1.22; P=0.45; I2 0%, respectively). Colchicine increased the risk for gastrointestinal side effects (P<0.001). According to trial sequential analyses, there is only sufficient evidence for a myocardial infarction risk reduction with colchicine. Conclusions Among patients with CAD, colchicine reduces the risk of myocardial infarction and stroke, but has a higher rate of gastrointestinal upset with no influence on all-cause mortality.